THE INFLUENCE OF BRAND AMBASSADOR, BRAND AWARENESS, AND BRAND IMAGE ON CONSUMER BUYING INTEREST - Safitri, Devi; Purnomo, Nanto (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
This study aims to determine whether there is an influence of each concept of variables from brand ambassador, brand awareness, and brand image on consumer purchasing interest in case study: mogu-mogu x seventeen on the autobase twitter account @caratstalk. The research method applied is a quantitative method with a descriptive approach. The results of the study found that each variable has a positive and significant influence on consumer purchasing interest in followers of the @caratstalk account on X from the Mogu-Mogu x Seventeen product. Brand Ambassador, Brand Awareness, and Brand Image Seventeen from the Mogu-Mogu product on followers of the @caratstalk account on social mediabrand through social media, especially on the @caratstalk account platform. High brand awareness or brand awareness influences the desire to buy Mogu-Mogu products